PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN BUAS-BUAS (Premna cordifolia. LINN) TERHADAP KADAR MDA TIKUS WISTAR JANTAN PASCA PAPARAN ASAP ROKOK - Asri Adyttia; Eka Kartika Untari; Sri Wahdaningsih (Faculty of Pharmacy, Universitas Muslim Indonesia, 2014)
Free radical from cigarrete smoke can cause lipid peroxidation that could lead to tissue damage. Tissue damage can be identified by increased levels of MDA (Malondialdehyde). Leavesof buas-buas (Premna cordifolia. Linn) has an antioxidant activity in invitro study. This study aimed to analyze the effect of P. cordifolia leaves extract on the levels of malondialdehyde (MDA) after exposure to cigarette smoke. The simplicia extracted by maseration using 70% ethanol. Twenty four wistar strain of Rattus novergicus were divided into six groups , i.e. : normal group without any treatment, positive control group with cigarette smoke exposure and vitamin e treatment, negative control groupwith only cigarette smoke exposure, treatment groupwith cigarette smoke exposure and ethanolic extract from P. cordifolialeaves with doses 200; 400; 600 mg/kg of body weight/day. All rats were treated for 14 days using 3 cigarette non filetered each day. After 14 days, plasma MDA was measured in this research. Measurement of plasma MDA are using Spectrophotometer UV-Vis in 532.2 nm. MDA level in this study was analyzed by the Kruskal-Wallis and Mann-Whitney test. The result showed that plasma MDA level of groupreceived ethanol extract of P. cordifolia leaves doses at 600 mg/kg of body weight/day significantly (p<0.05)lower than negative control group and not significantly differ (p<0.05) to normal group and positive control group.